Assessment of climate change on wheat (Triticum aestivum) production using crop simulation under Indo-Gangetic Plains - SINGH, MANVENDRA; MISHRA, G C; MALL, R K (The Indian Journal of Agricultural Sciences, 2022)
Climate change has very wide impact on different crops and cropping system. In north India crop like wheat also affected due to climate change. To assess the impact of climate change a study using CERES (Crop Environment Resource Synthesis) model was carried out at Kanpur, India. Three different levels of carbon dioxide (CO2) i.e. 450 ppm, 500 ppm and 550 ppm and two different levels of temperature (1̊C and 2̊C) and their interaction were used to study the impact of climate change on wheat production. The results revealed that different elevated levels of carbon dioxide concentration recorded higher production of wheat which ranges from 3–8%. Graded levels of temperatures caused drastic reduction in yield which ranges from 10–17%. Conjoint effect of temperature and carbon dioxide recorded yield losses from 1–16%.